2011
DOI: 10.1152/ajpregu.00026.2011
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of food intake by cholecystokinin requires activation of hindbrain NMDA-type glutamate receptors

Abstract: injection of CCK reduces food intake and triggers a behavioral pattern similar to natural satiation. Reduction of food intake by CCK is mediated by vagal afferents that innervate the stomach and small intestine. These afferents synapse in the hindbrain nucleus of the solitary tract (NTS) where gastrointestinal satiation signals are processed. Previously, we demonstrated that intraperitoneal (IP) administration of either competitive or noncompetitive N-methyl-D-aspartate (NMDA) receptor antagonists attenuates r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 50 publications
1
31
0
1
Order By: Relevance
“…Nevertheless, activation of this vagal gut-brain axis is vital for nutrient-triggered negative feedback, since treating the gut with anesthetics, neurotoxins, or vagotomy abolishes the effects of intestinal nutrients on food intake and glucose regulation (Schwartz, 2011). Vagal afferent fibers terminate in the nucleus tractus solitarius (NTS) of the hindbrain, and antagonism of N-methyl-D-aspartate (NMDA) receptors in the NTS reverses the effects of intestinal nutrients or CCK to lower food intake or suppress HGP (Cheung et al, 2009;Wang et al, 2008;Wright et al, 2011). Intestinal CCK-mediated activation of NTS NMDA receptors leads to MAPK-ERK1/2 signaling and phosphorylation of synapsin I in hindbrain neurons (Campos et al, 2012), and through unclear mechanisms, these neurons act as a relay for vagal gut-derived signals to control food intake or suppress HGP via the hepatic vagal efferent (Wang et al, 2008).…”
Section: Intestinal Nutrient Sensingmentioning
confidence: 99%
“…Nevertheless, activation of this vagal gut-brain axis is vital for nutrient-triggered negative feedback, since treating the gut with anesthetics, neurotoxins, or vagotomy abolishes the effects of intestinal nutrients on food intake and glucose regulation (Schwartz, 2011). Vagal afferent fibers terminate in the nucleus tractus solitarius (NTS) of the hindbrain, and antagonism of N-methyl-D-aspartate (NMDA) receptors in the NTS reverses the effects of intestinal nutrients or CCK to lower food intake or suppress HGP (Cheung et al, 2009;Wang et al, 2008;Wright et al, 2011). Intestinal CCK-mediated activation of NTS NMDA receptors leads to MAPK-ERK1/2 signaling and phosphorylation of synapsin I in hindbrain neurons (Campos et al, 2012), and through unclear mechanisms, these neurons act as a relay for vagal gut-derived signals to control food intake or suppress HGP via the hepatic vagal efferent (Wang et al, 2008).…”
Section: Intestinal Nutrient Sensingmentioning
confidence: 99%
“…Our use of D-CPP-ene was based on our prior experience with the antagonist and its effectiveness in blocking CCK-induced reduction of food intake when injected into the fourth ventricle or NTS (13,61). In addition, functional electrophysiological experiments indicate that D-CPPene effectively blocks NMDAR participation in vagus-to-NTS synaptic transmission (63).…”
Section: Discussionmentioning
confidence: 99%
“…In a crossover, counterbalanced experimental design, overnight-fasted rats (16 h) received a fourth ventricle injection of saline (0.9% NaCl), MTII (50 pmol; Phoenix Pharmaceuticals, Burlingame, CA), D-4-[(2E)-3-phosphono-2-propenyl]-2-piperazinecarboxylic acid (D-CPP-ene; 40 ng; Tocris, Ellisville, MO), or a cocktail containing D-CPP-ene and MTII in the above amounts. The selection of D-CPP-ene was based on our prior experience with the antagonist and its effectiveness in being able to block CCK-induced reduction of food intake when injected into the fourth ventricle or NTS (14,61). In addition, functional electrophysiological experiments indicate that D-CPP-ene effectively blocks NMDAR-dependent contributions in vagus-to-NTS neurotransmission (63).…”
Section: Effect Of Hindbrain Nmdar Antagonist Administration On Mtiiimentioning
confidence: 99%
See 1 more Smart Citation
“…MK801 has been reported to have off-target effects, interacting with other ion channels; however the NMDA receptor antagonists, AP5, and a NR2 subunit antagonist that distinguishes between different types of NMDA receptors, have also been shown to increase food intake in rats when injected into the medial NTS [49,50]. CCK-induced satiation, known to activate a vagal afferent pathway, was also found to be abolished by NTS injection of MK801 [51]. Neuro-anatomical studies demonstrated that exogenous CCK administration activated neurons in the medial NTS, and that activation of these neurons was abolished with NMDA receptor antagonists [51,53].…”
Section: Evidence That Glutamate Is Involved In Feedingmentioning
confidence: 99%